Organizational-methodical basis of a long-term training among greco-roman style wrestlers - Kuznetsov, A. S. (The Russian Journal of Physical Education and Sport, 2016)
There is the opinion in the theory of sport that in difficult coordinating, situational and psycho-stress kinds of sport the first place belongs to technical-tactical training with a gradual, in age-related aspect, subjected to it increase of functional loads. Sport wrestling, concerning this aspect, has not used considerable potential of technical-tactical training quality improvement and mass character by means of the following: